Advanced lifting system design for construction application - Pratik Balu Mahajan (2017)
In this 21st century the cities are growing smarter and bigger. And in country like Singapore the city is growing taller. The flowing report elaborated on the designing of a mechanism for the construction application. Tower cranes are the stationary cranes used for the construction applications. The specific design allows them to stand tall and manoeuvre in 360 degrees. This crane has a specific characteristic design which allows it to make numerous configurations in height and the jib length. This ability to adapt to the ongoing changes makes it the most acceptable machine for the tall cities such as Singapore. This crane operates at different heights and load which makes it difficult to operate and need the planning for the lifting operations prior lifting. This is made possible by using the advanced Virtual reality tools such as Computer-aided Engineering. The simulation of the Dynamics of the crane are done using the NTU crane simulator. The simulator provide the actual working site and environment for the lifting operations, which applies all the real time forces and load providing the accurate data to perform the operation with safety and perfection. Simulation as a computer tool is effective in modelling complex operations and construction planning. [Al-Hussein, M., Niaz, M. A., Yu, H., & Kim, H. (2006)] The Crane simulators accuracy depends upon the tower crane model, Modelling of different types and configurations is performed using the Computer Aided Design software's that is 3D modelling software's such as Autodesk Inventor, 3Ds MAX and solid works. The model are validated in the simulator. This results are used to design the whole family of the tower cranes by implementing the Product Family Approach. At last this family of cranes is used to generate real time, accurate, results for the planning of complex lifting processes.